Cultural-historical analysis of the pedagogy of learners with disabilities in Ghanaian Early Childhood Education - Muthivhi, Azwihangwisi (University of Pretoria, 2025)
Thesis (PhD (Early Childhood Education))--Univeristy of Pretoria, 2024.